(untitled) (Bangladesh Journal of Agricultural Research, 2008)
An efficient protocol was developed for plant regeneration, multiplication and rooting under in vitro condition in pointed gourd. Highest percent of shoot regeneration was 93.86 when nodal explants were cultured on MS+2.0 mg/1 BAP. The maximum number of shoots (4.00) per explant was observed in MS + 2.0 mg/1 BAP + 0.3 mg/1 NAA from nodal segment. Among the two explants, nodal segment was found better for shoot regeneration. Female genotypes responded better than the male genotypes for shoot induction and proliferation. Lower nodal segment performed the best shoot regeneration. The best response towards root induction was achieved on half MS medium supplemented with 0.5 mg/1 NAA. The regenerated plantlets were successfully established in prepared earthen soil pot. DOI: http://dx.doi.org/10.3329/bjar.v32i3.548 Bangladesh J. Agril. Res. 32(3) : 461-471, September 2007